REGIONAL LEVEL ANALYSIS OF THE PARLIAMENTARY CONTROL SYSTEM OF THE EXECUTIVE POWER ON THE EXAMPLE OF ADJARA - Genady Iashvili; Fati Khalvashi; Manvelidze, Irakli (International Journal of Innovative Technologies in Social Science, 2022)
In modern developed democracies, the mechanism of control of the executive structure by the representative body operates at both the central and local levels of government. In the case of Georgia, the analysis of the regional level is important, because the autonomy of Adjara in the country creates an important regional level of governance, and therefore the purpose of this study is to determine how similar mechanisms are represented in the regional governance system and how it works. To achieve this goal and to study this issue, is used a conceptual approach of social control. The research is based on quantitative and qualitative social research techniques, as well as analysis and statistical methods. All this helped us in proper analysis and study of collected primary and secondary scientific information and materials. This study was conducted between May 20 to August 20, 2022. According to the results of this research, in the presented study, the significance of the control of the representative body as a system at the regional level is studied for the first time. The functioning system and mechanisms of parliamentary control management at the regional level are shown and described. The parliamentary control system is defined as a characteristic of the transparent system of public administration. The quality of regional level parliamentary control management system is shown; Evaluation and measurement criteria. The problems of effective functioning of regional parliamentary control as a management system in Georgia are listed, and in the process of research we have developed recommendations that will contribute to the effectiveness of regional parliamentary control.